Morfhotectonical Units of Costa Rica: Characterization andPotencial for Enviromental Management - Arroyo-Solórzano, Mario; Quesada-Román, Adolfo (Revista Geográfica de América Central., 2025)
The tectonic and geomorphological dynamics of Costa Rica result from the interaction of four tectonic plates in a subduction zone, combined with tropical erosive processes. In this study, we extensively review the classifications and boundaries between morphotectonic units in Costa Rica. We propose an initial subdivision based on tectonic-structural elements and morphotectonic regions, whereby we establish thirteen main morphotectonic units that encompass similar relief and geomorphological characteristics. Finally, we analyze and related this classification with climatic factors, vegetation, dynamic geomorphology, soils, and land uses, where we evaluate common characteristics and highlight their potential use as a starting input for environmental planning.